Acute toxicity of benzophenone-type UV filters for Photobacterium phosphoreum and Daphnia magna: QSAR analysis, interspecies relationship and integrated assessment. (September 2015) - Liu, Hui; Sun, Ping; Liu, Hongxia; Yang, Shaogui; Wang, Liansheng; Wang, Zunyao
Highlights: Toxicity of 13 BPs to P. phosphoreum and D. magna was determined. QSARs were developed using DFT and CoMFA descriptors. The toxicity of BPs to P. phosphoreum is mainly related to electronic properties. The toxicity of BPs to D. magna is mainly related to hydrophobicity. An approach to evaluate the overall biological effect was proposed. Abstract: The hazardous potential of benzophenone (BP)-type UV filters is becoming an issue of great concern due to the wide application of these compounds in many personal care products. In the present study, the toxicities of BPs to Photobacterium phosphoreum and Daphnia magna were determined. Next, density functional theory (DFT) and comparative molecular field analysis (CoMFA) descriptors were used to obtain more detailed insight into the structure – activity relationships and to preliminarily discuss the toxicity mechanism. Additionally, the sensitivities of the two organisms to BPs and the interspecies toxicity relationship were compared. Moreover, an approach for providing a global index of the environmental risk of BPs to aquatic organisms is proposed. The results demonstrated that the mechanism underlying the toxicity of BPs to P. phosphoreum is primarily related to their electronic properties, and the mechanism of toxicity to D. magna is hydrophobicity. Additionally, D. magna was more sensitive than P. phosphoreum to most of the BPs, with the exceptions of the polyhydric BPs. Moreover, comparisons with published data revealed a high interspecies correlation coefficient among the experimental toxicity values for D. magna and Dugesia japonica . Furthermore, hydrophobicity was also found to be the most important descriptor of integrated toxicity. This investigation will provide insight into the toxicity mechanisms and useful information for assessing the potential ecological risk of BP-type UV filters.